QT INTERVAL IN CARDIOLOGIC CLINICS - Kulyk, V.L.; Iabluchanskyi, M.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
QT interval, reflecting depolarization and repolarization processes, and finally, ventricles ejection function has key value in cardiac activity. As response for structure and function abnormalities of cardiomyocytes ion channels, pathological states, drug effects, QT may change both prolongation and shortening. In review presented collected data on QT and its’ dispersion changes in main pathological states and effects of various drug groups.